The global burden of trachoma: a review. - Matthew J Burton; David C W Mabey (PLoS Neglected Tropical Diseases, 2009)
Trachoma is the commonest infectious cause of blindness worldwide. Recurrent infection of the ocular surface by Chlamydia trachomatis, the causative agent, leads to inturning of the eyelashes (trichiasis) and blinding corneal opacification. Trachoma is endemic in more than 50 countries. It is currently estimated that there are about 1.3 million people blind from the disease and a further 8.2 million have trichiasis. Several estimates for the burden of disease from trachoma have been made, giving quite variable results. The variation is partly because different prevalence data have been used and partly because different sequelae have been included. The most recent estimate from the WHO placed it at around 1.3 million Disability-Adjusted Life Years (DALYs). A key issue in producing a reliable estimate of the global burden of trachoma is the limited amount of reliable survey data from endemic regions.